Does Political Reservation for Minorities Affect Child Labor? Evidence from India - Elizabeth Kaletski; Nishith Prakash (Institute for the Study of Labor (IZA), 2014)
This paper examines the impact of state level political reservation for two minority groups Scheduled Castes and Scheduled Tribes on child labor in India. We estimate the effect of political reservation on child labor by exploiting the state variation in the share of seats reserved for the two groups in state legislative assemblies mandated by the Constitution of India. Using data from state and household level surveys on fifteen major Indian states, we find that at the household level, Schedule Tribe reservation decreases the incidence of child labor, while Scheduled Caste reservation increases the total number of children working. Our results survive a variety of robustness checks and potential explanations for the differential impact of SC and ST political reservation are also explored, including geographic isolation, caste fragmentation, support for the Congress Party, and decentralization of power.
Keywords: I38; J15; J22; J78; 330; affirmative action; minorities; child labor; India